The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10565-006-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

DA-9601 inhibits activation of the human mast cell line HMC-1 through inhibition of NF-κB

Abstract: Mast cell-mediated allergic inflammation is involved in many diseases such as asthma, sinusitis, and rheumatoid arthritis. Mast cells induce synthesis and production of pro-inflammatory cytokines including tumor necrosis factor (TNF)-alpha, interleukin (IL)-1beta and IL-6 with immune regulatory properties. The formulated ethanol extract of Artemisia asiatica Nakai (DA-9601) has been reported to have antioxidative and anti-inflammatory activities. In this report, we investigated the effect of DA-9601 on the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…DA-9601 is known to exert anti-inflammatory activity [25,26]. We also previously showed that the expression of TNF-α was inhibited by DA-9601 in activated human mast cells [13]. Therefore, we speculate that the inhibitory effect of DA-9601 on leukocyte infiltration in our AD model might be mediated by blocking TNF-α expression and downstream chemokines/adhesion molecules.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…DA-9601 is known to exert anti-inflammatory activity [25,26]. We also previously showed that the expression of TNF-α was inhibited by DA-9601 in activated human mast cells [13]. Therefore, we speculate that the inhibitory effect of DA-9601 on leukocyte infiltration in our AD model might be mediated by blocking TNF-α expression and downstream chemokines/adhesion molecules.…”
Section: Discussionmentioning
confidence: 58%
“…In the present report, we clearly showed the effect of DA-9601 on the AD; however, the molecular target of this effect is still unknown. We previously reported the anti-allergic inflammatory effect of DA-9601 through the inhibition of immediate-type hypersensitivity, histamine release and serum IgE, and pro-inflammatory cytokines by the attenuation of NF-κB [13,30]. The intracellular calcium and cAMP are the most important signaling pathways to the degranulation of mast cells and downstream histamine release [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. asiatica has been widely used for centuries in traditional Asian diets and medications without any serious side effects. We previously reported that the anti-allergic and anti-tumor properties of eupatilin in gastric epithelial cells and mast cells (Choi et al, 2008(Choi et al, , 2009Lee et al, 2007Lee et al, , 2008. In addition, the standardized ethanol extract of A. asiatica, DA-9601, has been shown to have strong anti-oxidative effects in experimental animal models, such as esophageal mucosal damage (Choi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This assay nonetheless gave a clear indication of toxicity against HeLa cells through indications of cell shrinkage or cells floating following exposure to the extracts (carrier solvent controls did not show any of these indicators of toxicity). The active species from this set, for which previous studies exist, include Turkish (Yesilada et al, 1997;Yesilada and Kupeli, 2007), East Asian (Suh et al, 2006;Park et al, 2006a) and Australian species of Clematis ; species of Artemisia from China (Jin et al, 2004;Lee et al, 2007) and Tibet (Sun et al, 2006). As identified in Jin et al (2004) sesquiterpene lactones are the likely NF-B inhibitors found in extracts of Artemisia spp.…”
Section: Speciesmentioning
confidence: 99%